General Practitioners' recommendations of self-directed-exercises for musculoskeletal problems and perceived barriers and facilitators to doing so: a mixed methods study - Toby Gillman; Kelly Ann Schmidtke; Victoria Manning; Ivo Vlaev (BMC, 2018)
Abstract Background Musculoskeletal problems substantially impact the demand for and the finances of the United Kingdom's National Health Service. Some of this demand and cost could be alleviated if patients use self-directed-exercises. The present study aims first to establish whether general practitioners already recommend self-directed-exercises and second to describe barriers and facilitators to making such recommendations. Method The design of the current study included surveys and interviews. The surveys were designed to draw out participants' tendency to recommend self-directed-exercises and their behavioral drivers to do so. The drivers investigated include 14 domains described by the Theoretical Domains Framework. The surveys were completed online and the responses were analyzed using descriptive reports and regression analyses. The interviews were designed to more fully understand participants' experiences recommending self-directed-exercises according to the same framework. The interviews were audio-taped, transcribed, and thematically analyzed. Results The survey found that the following domains significantly predicted participants' tendency to recommend self-directed-exercises: Environmental contexts and resources, Goals, Intentions, Knowledge, Memory attention and decision processes, and Social/professional role. The interviews brought out four themes that could be leveraged to increase general practitioners' tendency to recommend self-directed-exercises: (1) Practitioners' beliefs about self-directed-exercises being effective, (2) Patients' motivations to engage in self-directed-exercises, (3) Time constraints, and (4) The ease with which practitioners can recommend self-directed-exercises. Conclusions Most general practitioners already recommend self-directed-exercises, though they note significant barriers that may prevent them from doing so. General practitioners' tendency to recommend self-directed-exercises would be bolstered by creating a respected central resource of exercise pamphlets. These pamphlets should clearly describe how different self-directed-exercises should be performed and evidence supporting their effectiveness.